2017
DOI: 10.1177/0271678x17718966
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercise prevents rarefaction of pial collaterals and increased stroke severity that occur with aging

Abstract: Variation in extent of the brain's collateral circulation is an important determinant of variation in the severity of stroke and efficacy of revascularization therapies. However, the number and diameter of pial collateral "arterioles" decrease with aging in associated with reduced eNOS and increased oxidative stress. We tested whether exercise reduces this aging-induced rarefaction. Twelve-month-old mice were randomized to sedentary or voluntary wheel-running. At 26 months' age, permanent MCA occlusion was fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…B6.CX 3 CR 1 −/− were B6.129P(Cg)-Ptprc a Cx3cr1 tm1Litt /LittJ. B6.eNOS transgenic mice have a twofold increase in NO production [ 32 ]. Approximately, equal numbers of males and females were studied in each experiment.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…B6.CX 3 CR 1 −/− were B6.129P(Cg)-Ptprc a Cx3cr1 tm1Litt /LittJ. B6.eNOS transgenic mice have a twofold increase in NO production [ 32 ]. Approximately, equal numbers of males and females were studied in each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, the observed effects of sex were negligible for native pial collateral number, diameter, and amount of rarefaction seen with aging in 3.5-, 8-, and 22-month-old B6 mice or 8 versus 18-month-old B6; 129SvEv mice [ 43 ]. Angiography was performed after perfusion-fixation at maximal dilation and filling of the pre-capillary vessels with viscosity-adjusted Microfil ® [ 32 ]. All pial collaterals between the ACA and MCA trees of both hemispheres were identified and their anatomic (maximally dilated) lumen diameters were measured at midpoint and averaged for each animal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations